Phylogeny and Ecology of Trebouxia Photobionts From Bolivian Lichens - Kosecka, Magdalena; Kukwa, Martin; Jabłońska, Agnieszka; Flakus, Adam; Rodriguez-Flakus, Pamela; Ptach, Łucja; Guzow-Krzemińska, Beata (Frontiers in Microbiology, 2022)
In the past few years, new phylogenetic lineages in Trebouxia were detected as a result of molecular approaches. These studies included symbiont selectivity in lichen communities, transects along altitudinal gradients at local and global scales and the photobiont diversity in local populations of lichen-forming fungal species. In most of these studies, phylogenetic and haplotype analysis based on the ITS locus have continuously allowed the recognition of new monophyletic lineages, which suggests that still numerous undiscovered Trebouxia lineages can be hidden in lichens from unexplored areas, especially in the tropics. Here we estimated the biodiversity of photobionts in Bolivian Andean vegetation, and assessed their specificity. 403 lichen samples representing 42 genera, e.g., Haematomma, Heterodermia, Hypotrachyna, Lecanora, Lepra, Leucodermia, Parmotrema, Pertusaria, Polyblastidium and Usnea, containing Trebouxia photobionts were analysed. ITS rDNA and rbcL markers were used. We obtained Trebouxia sequences from Bolivian samples belonging to already described clades A, C, I and S. Thirty nine Trebouxia lineages were distinguished within these clades, while 16 were new. To reveal the structure of the community of Bolivian photobionts and their relationships with mycobionts, comparative effects of climate, altitude, geographical distances, substrate, and habitat type, as well as functional traits of lichens such as growth forms, propagation mode and secondary chemistry, were analysed. Furthermore, new Bolivian records were included in analysis on a global scale. In our study, the mycobiont genus or even species are the most important factors correlated with photobiont identity. Moreover, we revealed that the community of Bolivian photobionts is shaped by altitude.